Risks associated with animal-assisted intervention programs: A literature review. (May 2020) - Dalton, Kathryn R.; Waite, Kaitlin B.; Ruble, Kathy; Carroll, Karen C.; DeLone, Alexandra; Frankenfield, Pam; Serpell, James A.; Thorpe, Roland J.; Morris, Daniel O.; Agnew, Jacqueline; Rubenstein, Ronald C.; Davis, Meghan F.
Abstract: The benefits of animal-assisted interventions (AAI), to utilize companion animals as an adjunctive treatment modality, is well-established and a burgeoning research field. However, few studies have evaluated the potential hazards of these programs, such as the potential for therapy animals to transfer hospital-associated pathogens between individuals and the hospital environment. Here we review the current literature on the possible risks of hospital-based AAI programs, including zoonotic pathogen transmission. We identified twenty-nine articles encompassing reviews of infection control guidelines and epidemiological studies on zoonotic pathogen prevalence in AAI. We observed substantial heterogeneity in infection control practices among hospital AAI programs. Few data confirmed pathogen transmission between therapy animals and patients. Given AAI's known benefits, we recommend that future research utilize a One Health framework to evaluate microbial dynamics among therapy animals, patients, and hospital environments. This framework may best promote safe practices to ensure the sustainability of these valuable AAI programs. Highlights: Despite benefits of animal-assisted interventions (AAI), there is a risk of therapy animals to spread hospital pathogens. There is an absence of literature on transmission of pathogens between patients and animals during an AAI session. More research is needed to improve the safety and utilization of this important adjunctive therapy.